Sichen Formula Ameliorates Lipopolysaccharide-Induced Acute Lung Injury via Blocking the TLR4 Signaling Pathways - Yan LS; Cui S; Cheng BCY; Yin XB; Wang YW; Qiu XY; Nima CR; Zhang Y; Zhang SF (Dove Medical Press, 2023)
Li-Shan Yan,1,* Shuang Cui,1,* Brian Chi-Yan Cheng,2 Xing-Bin Yin,1 Yi-Wei Wang,1 Xin-Yu Qiu,1 Ci-Ren Nima,3 Yi Zhang,1 Shuo-Feng Zhang1 1School of Chinese Materia Medica, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 2College of Professional and Continuing Education, Hong Kong Polytechnic University, Hong Kong, People's Republic of China; 3Tibetan Traditional Medical College, Lhasa, Tibet, People's Republic of China*These authors contributed equally to this workCorrespondence: Shuo-Feng Zhang; Yi Zhang, School of Chinese Materia Medica, Beijing University of Chinese Medicine, No. 11, Bei San Huan Dong Lu, Chaoyang District, Beijing, 100029, People's Republic of China, Tel/Fax +86-10-53912122, Email shuofengzhang@sina.com; yizhang714@163.comPurpose: Sichen (SC) formula is a classic prescription of Tibetan medicine. Due to its potential anti-inflammatory effect, the SC formula has been clinically used to treat respiratory diseases for many years in the Chinese Tibet region. The present study aimed to investigate the anti-inflammatory effect of SC and explore the underlying mechanisms.Methods: SC formula was characterized by HPLC analysis. The acute lung injury (ALI) mouse model was induced by direct intratracheal lipopolysaccharide (LPS) instillation, and bronchoalveolar lavage fluid (BALF) and lung tissues were collected. Meanwhile, RAW264.7 macrophages were stimulated by LPS. The contents of inflammatory mediators in the culture medium were determined by ELISA. Protein levels were determined by immunohistochemical staining or Western blotting. Nuclear localization of NF-κB, AP-1, and IRF3 was performed using immunofluorescence and Western blotting.Results: In the LPS-induced ALI mouse model, SC treatment suppressed the secretion of inflammatory mediators (TNF-α, IL-6, IL-1β, MCP-1, MIP-1α, and RANTES) in BALF. SC treatment hindered the recruitment of macrophages. SC treatment also inhibited the expression of CD68, p-p65, and TLR4 in the lung tissue. In the LPS-exposed RAW264.7 cells, the cell viability was not changed up to 400 μg/mL of SC. SC concentration-dependently suppressed the production of nitric oxide, prostaglandin E2, TNF-α, IL-6, MCP-1, MIP-1α, and RANTES in LPS-challenged RAW264.7 cells. The expression levels of iNOS, COX-2, p-p38, p-JNK, p-ERK, p-TBK1, p-IKKα/β, p-IκB, p-p65, p-c-Jun, and p-IRF3 were decreased after SC treatment. Moreover, the nuclear translocation of p65, c-Jun, and IRF3 was also blocked by SC treatment.Conclusion: SC treatment inhibited the inflammatory responses in LPS-induced ALI mouse model/RAW264.7 macrophages. The underlying mechanism of this action may be closely associated with the suppression of TLR4 signaling pathways. These research findings provide further pharmacological justifications for the medicinal use of SC in the management of respiratory diseases.Keywords: Sichen formula, acute lung injury, RAW264.7 macrophages, lipopolysaccharide, TLR4 signaling pathways